Deaf interpreters at work : international insights - Adam, Robert (Studies in Interpretation ;, 2014)
Now, for the firs time, a collection featuring 17 widely respected scholars depicts the everyday practices of deaf interpreters in their respective nations. The 11 th volume inthe studies in interpretation series presents the history of Deaf translators and interpreters and details the development of testing and accreditation to raise their professional profiles. Other chaters delineate the cognitive processes of Deaf Interpreting: Deaf-Deaf interpreter teams; Deaf and hearing for the Deaf Blind community; and conference interpreting and interpreting teams.